Pengaruh Work Life Balance dan Burnout Terhadap Kinerja Pegawai Pemerintah Generasi Milenial - Robert Imanuel; Hendy Tannady (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze how work-life balance (WLB) and burnout affect employee performance (EP) among millennial government employees in Jakarta from three institutional groups. The research subjects include Civil Servants (ASN), Government Employees with Work Agreements (PPPK), and other service providers (PJLP). This study uses a quantitative approach with 235 millennial employees as respondents. The data was analyzed using Structural Equation Modeling (SEM). The findings show that WLB has a positive effect on employee performance, while burnout has a negative relationship with work performance. This indicates that increased life balance has the potential to boost productivity, while work fatigue actually reduces employee effectiveness. Additionally, the research results emphasize how decisions implemented in government agencies can contribute to supporting the performance of millennial employees and creating a healthy work environment. These strategies not only help improve the performance of millennial employees but also support the achievement of a balance between their work and personal lives.